Nephroprotective and Hepatoprotective Effects of Ethanol Extract of Eleutherine bulbosa (Mill) Urb in Hypertensive and Hyperlipidaemic Rats - Kaffah, Silmi; Bachri, Moch Saiful; Laela Hayu Nurani; Daru Estiningsih; Danang Prasetyaning Amukti; Muhammad Ma’ruf (Scripta Medica, 2025)
Background/Aim: Hypertension and hyperlipidaemia are interrelated conditions that elevate the risk of cardiovascular diseases and contribute to the dysfunction of critical organs such as the liver and kidneys. Eleutherine bulbosa (Mill) Urb, known as Dayak onion, contains bioactive compounds like flavonoids, phenolics, quercetin derivatives and oxyresveratrol, which are believed to have nephroprotective and hepatoprotective effects due to their antioxidant and anti-inflammatory properties. This study aimed to evaluate the protective effects of the ethanol extract of Dayak onion on kidney and liver function in hypertensive and hyperlipidaemic rats. Methods: The experimental design employed a pre-post-test control group over 28 days. Thirty-five male Wistar rats were divided into seven groups: Normal group, Negative control (given NaCl solution at a dose of 3.75 g/kg body weight and fed a high-fat diet), Positive control (captopril and simvastatin) and three Treatment groups (given Dayak onion ethanol extract (EEEB) suspension at doses of 100, 200 and 400 mg/kg body weight, respectively). Serum was extracted via the ophthalmic vein on days 22 and 29.Results: Compared to the negative control group, this study showed that administering doses of 100, 200 and 400 mg/kg BW of EEEB was able to significantly lower blood urea nitrogen (BUN), creatinine, alanine transaminase (SGPT) and aspartate aminotransferase (SGOT) levels (p < 0.05). The dose of 400 mg/kg BW demonstrated the highest potential to protect the kidneys and liver, coming close to or matching the effects seen in the positive control group. In addition, the protective effect of EEEB on the kidneys and liver was compared to the positive control group (captopril and simvastatin). Conclusion: Based on these findings, it can be concluded that EEEB protects against kidney and liver damage caused by hypertension and hyperlipidaemia.
Keywords: Dayak onion; Blood urea nitrogen; Creatinine; Alanine transaminases; Aspartate aminotransferases; Hypertension; Hyperlipidaemias